1997
DOI: 10.1007/s004220050399
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical illusions: study and modelling

Abstract: The phenomena of geometrical illusions of extent suggest that the metric of a perceived field is different from the metric of a physical stimulus. The present study investigated the Müller-Lyer and Oppel-Kundt illusions as functions of spatial parameters of the figures, and constructed a neurophysiological model. The main idea of the modelling is based on the uncertainty principle, according to which distortions of size relations of certain parts of the stimulus, so-called geometrical illusions, are determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 79 publications
3
43
0
1
Order By: Relevance
“…In our previous seeking of underlying principles behind the misperception of extent (Bulatov et al 1997, Bulatov and Bertulis 1999, the main attention was drawn to the cortical processes of spatial-frequency filtering. Since the computational procedures of the current model represent some calculations of convolution and spatial integration, it can be considered as a further development of the "filtering" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous seeking of underlying principles behind the misperception of extent (Bulatov et al 1997, Bulatov and Bertulis 1999, the main attention was drawn to the cortical processes of spatial-frequency filtering. Since the computational procedures of the current model represent some calculations of convolution and spatial integration, it can be considered as a further development of the "filtering" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a stimulus with a certain number of evenly allocated identical fillers induces a considerably stronger illusion than that with an irregular distribution (Lewis 1912, Noguchi 2003 or with many fillers fused into one continuous unit (Bailes 1995, Bertulis andBulatov 2001). At the same time, the region of the illusion maximum was relatively flat and varied between studies: the greatest effect was found for the number of fillers from 11 to 23 (Spiegel 1937), 9 to 14 (Piaget and Osterrieth 1953), 4 to 13 (Bulatov et al 1997), 11 to 13 (Wackermann and Kastner 2010), and 8 to 12 (Mikellidou and Thompson 2014). If the stimulus elements differed in shape or size then the effect of the illusion was substantially diminished (Obonai 1954, Wackermann and Kastner 2009, Wackermann 2012a.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…So, the inward-pointing arrowheads have large inter-tip distances that "stretch" the perceived line length and the outward-pointing arrowheads have small inter-tip distances, compressing the perceived line length. This is not the only such explanation put forth for Muller-Lyer that implies a perceptual 'stretching' of the fins-in and 'compression' of the fins-out (for example, Bulatov et al (1997) spatial filter model, or Findlay (1982 'center of gravity' for alternatives). The work presented here is not intended to specifically test between these various alternatives, since for the most part, they will make similar predictions for the stimulus configurations employed.…”
Section: Introductionmentioning
confidence: 99%